Effect of porosity on the magneto-mechanical behavior of polycrystalline magnetic shape-memory Ni–Mn–Ga foams. (15th June 2015) - Witherspoon, C.; Zheng, P.; Chmielus, M.; Dunand, D.C.; Müllner, P.
Abstract: Porosity in polycrystalline Ni–Mn–Ga alloys reduces internal constraints imposed by grain boundaries which suppress magnetic-field-induced strain in non-porous, polycrystalline magnetic shape-memory alloys. We present here a systematic study of the porosity effect on the magneto-mechanical properties of polycrystalline Ni–Mn–Ga foams. Starting from replicated foams created by casting with ceramic space holders, their porosities were increased by successive acid dissolution steps after which the magnetic-field-induced strain was measured, for each porosity level, after thermo-magneto-mechanical training. Consistently, the magnetic-field-induced strain increased with increasing porosity, in the extreme case by one order of magnitude for a small porosity increase of 1.3%, demonstrating that removal of constraints by porosity is responsible for the high magnetic-field-induced strain in polycrystalline Ni–Mn–Ga foams.